ІНФОРМАЦІЙНО-ТЕХНОЛОГІЧНЕ ЗАБЕЗПЕЧЕННЯ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2012)
The article reveals the nature and characteristics of information technology support for the training of future teachers in the context of informatization of higher education; defines and substantiates its components: informational and technological; gives grounds for the importance of creating professionally oriented environment.